JavaScript : functional programming for JavaScript developers : unlock the powers of functional programming hidden within JavaScript to build smarter, cleaner, and more reliable web apps : a course in three modules.: functional programming for JavaScript developers : unlock the powers of functional programming hidden within JavaScript to build smarter, cleaner, and more reliable web apps : a course in three modules. (2016) - Antani, Ved; Timms, Simon; Mantyla, Dan
No abstract available